2024
DOI: 10.1002/hipo.23605
|View full text |Cite
|
Sign up to set email alerts
|

Theta and alpha oscillations in human hippocampus and medial parietal cortex support the formation of location‐based representations

Akul Satish,
Vanessa G. Keller,
Sumaiyah Raza
et al.

Abstract: Our ability to navigate in a new environment depends on learning new locations. Mental representations of locations are quickly accessible during navigation and allow us to know where we are regardless of our current viewpoint. Recent functional magnetic resonance imaging (fMRI) research using pattern classification has shown that these location‐based representations emerge in the retrosplenial cortex and parahippocampal gyrus, regions theorized to be critically involved in spatial navigation. However, little … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…It should be noted that an increase in theta power, in conjunction with spatial processing behaviours, has also been reported (e.g., Backus et al, 2016;Osipova et al, 2006;Pu et al, 2017). Recently, Satish et al, (2024) found that hippocampal and posteromedial cortical theta was enhanced when participants watched videos showing that previously viewed scenes were from the same location (rather than two different locations). They concluded that such theta power increases supported the formation of 'location-based representations'.…”
Section: Scene Processing May Be Supported By Theta Power Modulation ...mentioning
confidence: 91%
“…It should be noted that an increase in theta power, in conjunction with spatial processing behaviours, has also been reported (e.g., Backus et al, 2016;Osipova et al, 2006;Pu et al, 2017). Recently, Satish et al, (2024) found that hippocampal and posteromedial cortical theta was enhanced when participants watched videos showing that previously viewed scenes were from the same location (rather than two different locations). They concluded that such theta power increases supported the formation of 'location-based representations'.…”
Section: Scene Processing May Be Supported By Theta Power Modulation ...mentioning
confidence: 91%